The changing roles of neurons in the cortical subplate - Friedlander, Michael J.; Torres-Reveron, Juan (Frontiers in Neuroanatomy, 2009)
Neurons may serve different functions over the course of an organism’s life. Recent evidence suggests that cortical subplate neurons including those that reside in the white matter may perform longitudinal multi-tasking at different stages of development. These cells play a key role in early cortical development in coordinating thalamocortical reciprocal innervation. At later stages of development, they become integrated within the cortical microcircuitry. This type of longitudinal multi-tasking can enhance the capacity for information processing by populations of cells serving different functions over the lifespan. Subplate cells are initially derived when cells from the ventricular zone underlying the cortex migrate to the cortical preplate that is subsequently split by the differentiating neurons of the cortical plate with some neurons locating in the marginal zone and others settling below in the subplate (SP). While the cortical plate neurons form most of the cortical layers (layers 2-6), the marginal zone neurons form layer 1 and the SP neurons become interstitial cells of the white matter as well as forming a compact sublayer along the bottom of layer 6. After serving as transient innervation targets for thalamocortical axons, most of these cells die and layer 4 neurons become innervated by thalamic axons. However, 10-20% survives, remaining into adulthood along the bottom of layer 6 and as a scattered population of interstitial neurons in the white matter. Surviving subplate cells’ axons project throughout the overlying laminae, reaching layer 1 and issuing axon collaterals within white matter and in lower layer 6. This suggests that they participate in local synaptic networks, as well. Moreover, they receive excitatory and inhibitory synaptic inputs, potentially monitoring outputs from axon collaterals of cortical efferents, from cortical afferents and/or from each other. We explore our understanding of the functional connectivity of these cells at different stages of development.